Effect of students' background on microprocessor course performance / Norhayati Ahmad ... [et al.] - Ahmad, Norhayati; Md Enzai, Nur Idawati; Rais, Siti Sara; Mohamed, Syazilawati; Abd Ghani, Mohd Amir Hamzah; Ismail, Nuraiza (2017)
Academic performance of higher education students has always been given attention over the years. Numerous approaches have been proposed and implemented to improve academic performance as it reflects the students' comprehension of the lessons taught in university. Realizing the significance of academic achievement, Faculty of Electrical Engineering, UiTM Terengganu had conducted a study of Microprocessor course students' background. Even though Microprocessor is one of the courses which manage to garner highest achievement, the instructors have noticed that there is a decline in students' effort to excel in this course. Therefore, our work selects four criteria which reflect students' background namely: CGPA, previous secondary school, performance and interest in C programming course to study how each background criterion affects the performance. The survey responses which involved 38 students have shown that the students' performance in Microprocessor course is indeed affected by their CGPA, secondary school and grade in C programming course. Their interests in C programming do not leave huge impact on their performance. The findings will be used to take prevention step in the future for improvement of Microprocessor course performance. In consequence, this could contribute to achievement of faculty and university objectives.